WATER-ABSORPTION BY CORK - ROSA, M. E.; FORTES, M. A. (WOOD AND FIBER SCIENCE, 1993)
A study of liquid water absorption by cork was carried out in which the anisotropy of cork was taken into account. The changes with time of the mass, volume, and linear dimensions were measured for different orientations of the sections in cork exposed to liquid water at room temperature (20 C) and at 90-100 C. Two regimes of water absorption were identified, namely, a period involving dimensional change and a period with only mass change. Diffusion coefficients at both temperatures were estimated using a special technique. There is a small anisotropy with a faster diffusion in the radial direction. Diffusion coefficients at 90 C are two orders of magnitude larger than at room temperature. Water absorption in the cell walls causes the expansion of cork, which (for the boiled specimens tested) is slightly smaller in the radial direction. The volume increase is proportional to the mass increase and ceases after relatively short immersion times. At this stage, the cell walls are apparently saturated with water. Further immersion results in penetration of water into the cells. The kinetics of absorption is rather slow at long times, but eventually the cells become full of water, the density increases above that of water, and the cork sinks.
The following values have no corresponding Zotero field: pub-location: ONE GIFFORD PINCHOT DR, MADISON, WI 53705 USA publisher: SOC WOOD SCI TECHNOL
Keywords: Cork; DIFFUSION COEFFICEIENTS; DIMENSIONAL CHANGE; WATER ABSORPTION

A mass spectrometry study of thermal dissociation of cork - Filomena Bento, M.; Aurea Cunha, M.; Moutinho, A. M. C.; Pereira, H.; FORTES, M. A. (International Journal of Mass Spectrometry and Ion Processes, 1992)
Mass spectrometry has proved a convenient technique for the analysis of plant cell-wall material. In this work a comparative study is made of chemically treated cork and untreated cork, applying a method in which samples were continuously heated in vacuum. The outgassing products, upon electron-induced fragmentation, are analysed by a quadrupole mass spectrometer. Sequence of spectra at increasing temperatures were obtained for each sample, which allowed identification of the main groups of fragmentation. From such sequences of spectra one may derive intensity—temperature curves for each peak. Analysis of these curves for samples subjected to different treatments proved useful to identify the peaks, to assign the component which originates the species and even to derive activation energies.
Keywords: Cork; electron-induced fragmentation; thermal dissociation